Noncontrast Computed Tomography e-Stroke Infarct Volume Is Similar to RAPID Computed Tomography Perfusion in Estimating Postreperfusion Infarct Volumes. Issue 2 (February 2021) - Bouslama, Mehdi; Ravindran, Krishnan; Harston, George; Rodrigues, Gabriel M.; Pisani, Leonardo; Haussen, Diogo C.; Frankel, Michael R.; Nogueira, Raul G.
Abstract : Background and Purpose: The e-Stroke Suite software (Brainomix, Oxford, United Kingdom) is a tool designed for the automated quantification of The Alberta Stroke Program Early CT Score and ischemic core volumes on noncontrast computed tomography (NCCT). We sought to compare the prediction of postreperfusion infarct volumes and the clinical outcomes across NCCT e-Stroke software versus RAPID (IschemaView, Menlo Park, CA) computed tomography perfusion measurements. Methods: All consecutive patients with anterior circulation large vessel occlusion stroke presenting at a tertiary care center between September 2010 and November 2018 who had available baseline infarct volumes on both NCCT e-Stroke Suite software and RAPID CTP as well as final infarct volume (FIV) measurements and achieved complete reperfusion (modified Thrombolysis in Cerebral Infarction scale 2c-3) post-thrombectomy were included. The associations between estimated baseline ischemic core volumes and FIV as well as 90-day functional outcomes were assessed. Results: Four hundred seventy-nine patients met inclusion criteria. Median age was 64 years (55–75), median e-Stroke and computed tomography perfusion ischemic core volumes were 38.4 (21.8–58) and 5 (0–17.7) mL, respectively, whereas median FIV was 22.2 (9.1–56.2) mL. The correlation between e-Stroke and CTP ischemic core volumes was moderate (R=0.44; P <0.001). Similarly, moderate correlations were observed between e-Stroke software ischemic core and FIV (R=0.52; P <0.001) and CTP core and FIV (R=0.43; P <0.001). Subgroup analysis showed that e-Stroke software and CTP performance was similar in the early and late (>6 hours) treatment windows. Multivariate analysis showed that both e-Stroke software NCCT baseline ischemic core volume (adjusted odds ratio, 0.98 [95% CI, 0.97–0.99]) and RAPID CTP ischemic core volume (adjusted odds ratio, 0.98 [95% CI, 0.97–0.99]) were independently and comparably associated with good outcome (modified Rankin Scale score of 0–2) at 90 days. Conclusions: NCCT e-Stroke Suite software performed similarly to RAPID CTP in assessing postreperfusion FIV and functional outcomes for both early- and late-presenting patients. NCCT e-Stroke volumes seems to represent a viable alternative in centers where access to advanced imaging is limited. Moreover, the future development of fusion maps of NCCT and CTP ischemic core estimates may improve upon the current performance of these tools as applied in isolation. Abstract : Supplemental Digital Content is available in the text.